Efektivitas Penggunaan LKPD Interaktif Berbasis Liveworksheet dalam Meningkatkan Hasil Belajar Matematika Siswa Kelas XI Agama di MAS 2 Malang - Nugroho, Rahmat; Marhayati, Marhayati (Program Studi Tadris Matematika Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
This research aims to find out how effective the use of Liveworksheet-Based Interactive LKPD is in improving students' mathematics learning outcomes in class and Post-Test with 5 essay questions. The data analysis methods applied are normality test, homogeneity test and paired t test. From the data from the t test analysis results, there is a significant difference between learning outcomes in pre-test and post-test scores on derivative application material. And this is also proven by the results of the t test which received a significance of 0.00 < 0.05. If the significance value is <0.05, then H0 is rejected and it can be concluded that